Green synthesis of nano-copper oxide using Sargassum sp. functionalized in cellulose acetate membrane for dye adsorption - U. Yanuhar; H. Suryanto; M. Amin; J.S. Binoj; I. Casuarina (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Nanoparticles are presently employed in a multitude of applications due to their advantageous features, which encompass simplicity, non-toxicity, affordability, lack of pollutants, and environmentally friendly process. Utilization of Sargassum sp extract for producing nano-copper oxide is environmentally friendly. The study demonstrates the synthesis of nano-copper oxide facilitated by the macroalgae Sargassum sp. and its application in functionalizing cellulose acetate membrane to enhance dye adsorption capacity. The objective of the current study is to assess the properties of the green synthesis product of nano-copper oxide by employing Sargassum sp. macroalgae and its functionalized cellulose acetate membrane for the purpose of dye adsorption.METHODS: The preparation of Sargassum sp. extract involved utilizing quantities of 2.5, 5.0, and 10.0 grams, which were subsequently combined with a copper sulphate solution to yield nano-copper oxide. Nano-copper oxide was characterized using ultra violet-visual spectroscopy, scanning electron microscope - energy dispersive spectroscopy, x-ray diffraction, and fourier transform infrared techniques. Nano-copper oxide was introduced to bacterial acetate produced from pineapple peel waste to make a composite membrane and observed the antibacterial activity against E.coli and S.aureus, and dye adsorption to Methylene Blue, Malachite Green, Metanil Yellow, and Congo Red for 60 minutes contact time.FINDINGS: Nano-copper oxide is successfully synthesized using macroalgae Sargassum sp. proved by wavelength of ultra violet-visual spectroscopy results at 300 nanometer and energy dispersive spectroscopy analysis that denotes the presence of copper at 0.93 and 8.04 kilo electron volt. It has been verified that the inclusion of Sargassum sp. has effectively facilitated the production of nano-copper oxide. The findings from X-ray diffraction analysis reveal that the crystallite size of the nano-copper oxide measures approximately 19.5 nanometers. Adding nano-copper oxide as much as 2.0 weight percent into cellulose acetate membrane reduces membrane crystalline index from 88.6 percent to 85.7 percent but gives benefit in increasing the anti-bacterial activity against Escherichia coli and Staphylococcus aureus. The adsorption capacity is enhanced for Methylene Blue and Malachite green dyes, whereas it is diminished for Metanil Yellow and Congo Red dyes.CONCLUSION: Sargassum sp. was effectively employed as a reducing agent to synthesize nano-copper oxide, with an optimal concentration of 5.0 grams for achieving green synthesis. The copper metal obtained through green synthesis exhibits a spherical morphology and possesses an average crystallite size of approximately 19.5 nanometers. It has a percentage atomic weight of 60.6 percent. Introducing nano-copper oxide by 2.0 weight percent into bacterial cellulose acetate membrane reduces the crystalline index from 88.6 percent to 85.7 percent. The rise in nano-copper oxide content within the cellulose acetate membrane leads to a proportional increase in the membrane's antibacterial properties. Additionally, the adsorption of cationic dye in cellulose acetate composite is enhanced, while the adsorption of anionic dye is diminished.